Analisa Perbandingan Quality of Service Protokol VPN antara Protokol SSTP Dan Open VPN Berbasis Router Mikrotik - Surono; Guntoro Setiaji, Galet (AI Society & STMIK Indonesia, 2022)
The internet itself is a public network that can connect anyone into a very large network, and of course there are threats of data theft in it, VPN is a communication technology that allows an employee in the office to connect to a public network and use it to join the local network. . The advantage of a VPN is that the data sent via a VPN is encrypted so it is quite safe and the secret is maintained even though it is through the internet network, a comparison analysis of VPN performance between the SSTP (Secure Socket Tunneling Protocol) protocol and the Open VPN protocol will be carried out to determine the Quality Of Service (Qos) performance of both For this protocol, a study is needed to determine the use of the method so as to produce an optimal QOS (Quality of Service)